TRIANGLE operation for borderline resectable pancreatic cancer in total pancreatectomy - Zhai, Shuyu; Huo, Zhen; Wang, Yue; Qian, Hao; Zhao, Shulin; Shi, Yusheng; Weng, Yuanchi; Deng, Xiaxing; Shen, Baiyong (Translational Cancer Research, 2019)
Background: Pancreatic cancer is a highly aggressive cancer featured by early metastasis and multiple chemoresistance. Surgical resection remains the only way for the radical cure of pancreatic cancer. The aim of this study was to assess the safety, feasibility and oncological effect of the Heidelberg TRIANGLE operation in total pancreatectomy (TP) for borderline resectable pancreatic cancer (BRPC). Methods: Patients with BRPC eligible for TP were selected and underwent total pancreatectomy with Heidelberg TRIANGLE operation. Sharp dissection was applied to separate tumor and involved artery. Then we completely dissected the soft tissues surround celiac axis (CA) and superior mesenteric artery (SMA) in each case. If superior mesenteric vein (SMV) or portal vein (PV) were invaded by the tumor, resection and reconstruction of veins were performed. Operation time, blood loss, post-operative complications, perioperative mortality, number of lymph node examined and R0 resection rate were collected and analyzed. Results: Nine BRPC patients underwent TRIANGLE operation in TP. No perioperative death occurred. 3 cases developed postoperative complications: biliary leakage and colon fistula in 1 case and lymphatic leakage in 2 cases. The R0 resection rate of operation was 88.89% (8/9). Conclusions: For patients with BRPC, upfront surgery should be encouraged when they were unwilling or unable to received neoadjuvant therapy. Especially for those patients with artery involvement eligible for TP, TRIANGLE operation can help to achieve arterial sparing resection. Thus, the risk of postoperative hemorrhage for vascular reconstruction and skeletonization can be reduced. After postoperative adjuvant therapy, the prognosis is acceptable.